Penerapan Structural Equation Modelling-Partial Least Square pada Faktor-Faktor yang Memengaruhi Keputusan Pembelian Usaha MyCake.Ofc - Siti Nurmardia Abdussamad; Amanda Adityaningrum; Muhammad Rezky Friesta Payu; Syafri Yandi Kudo; Desya Neydi Putri Pakaya; Qamarani Zatil Isma Darise (Scimadly Publishing, 2026)
This study aims to analyze the influence of product, price, and promotion on purchasing decisions at MyCake.Ofc using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. Data were collected through questionnaires distributed to 100 respondents in Gorontalo City, selected using purposive sampling techniques. The analysis results show that price has a significant influence on purchasing decisions, while the product and promotion variables do not have a significant effect. The research model has an R-square value of 97.6%, indicating that the product, price, and promotion variables explain 97.6% of the variation in purchasing decisions.. This study highlights the importance of competitive pricing strategies to enhance consumer appeal and purchasing decisions in the food business sector, particularly at MyCake.Ofc.